A UK single-centre retrospective analysis of malaria diagnostics. (September 2019) - Merrick, Blair; Lambert, John; Schmid, Matthias L.
Highlights: Despite guideline recommendations, across both primary and secondary care, only a minority (< 16%) of individuals with a suspected diagnosis of malaria underwent serial blood film examination to exclude the diagnosis, should initial tests prove negative. However, over the seven-year study period, all 140 diagnoses of malaria made were on the first blood film sent to the laboratory for analysis. No additional diagnoses were made on the second, third, or further blood films sent for examination. The majority of cases of malaria were Plasmodium falciparum, in individuals with a history of recent travel to West and Central Africa. This study suggests that examination of a single blood film may be sufficient to exclude a suspected diagnosis of malaria in tertiary referral centres. Abstract: Objectives: The objective of the study was to assess adherence to current UK (2016) guidelines on the investigation of patients with suspected malaria, and if practice of analysing serial blood films is necessary to exclude a diagnosis of malaria in febrile returning traveller. Methods: All samples taken in 7-year period sent for the examination of malaria parasites to a tertiary referral tropical medicine centre were included in the analysis. Samples were separated into a total of 2082 patient episodes (all samples sent within 30 days of initial sample). Data were additionally collected on parasite subspecies and travel history. Results: Adherence to current malaria diagnostic guidelines is poor, especially for patients assessed in primary care. All positive diagnoses of malaria were made on initial blood film sent for analysis; negative predictive value of blood film with no malaria parasites was identified 100% in excluding diagnosis of malaria. Conclusions: Serial blood films may not be necessary to exclude diagnosis of malaria in specialist centres. Risk stratification of febrile patients returning from endemic world regions may help in selecting patients requiring further blood film analysis after initial negative film.